Frequency of hypoalbuminemia in acute ischemic stroke patients presenting at Ayub teaching hospital Abbottabad - Haq, Zia Ul; Jahangiri, Attique Ur Rehman; Hamza, Muhammad; Hussain, Nizakat; Ullah, Atiq; Shah, Qasim (International Journal of Pathology, 2025)
Background: Stroke is a condition with several contributing variables. Variations in blood albumin levels can have a significant impact on the severity, course, and outcome of the disease. The study’s objective is to determine the prevalence of hypoalbuminemia in patients who arrive at Ayub Teaching Hospital, Abbottabad with acute ischemic stroke. Methods: This Descriptive, cross-sectional study was conducted by Department of Medicine, Ayub Teaching Hospital, Abbottabad from January 2024 to June 2024.All patients who experienced an ischemic stroke between the ages of 30 and 70 were included, regardless of gender. Patients with a history of nephrotic syndrome, transient ischemic stroke, decompensated liver disease, protein-losing enteropathy, or other chronic conditions including severe heart failure were excluded. 165 patients were selected via non-probability sequential sampling. The informed consent of each patient was sought. Serum albumin levels were determined. Hypoalbuminemia is regarded as positive if the serum albumin level is less than 35 g/l. Results: Mean age was 56.85 ± 11.95 years. Of the 165 patients, 72 (43.64%) were female and 93 (56.36%) were male. The average BMI was 27.60 ± 3.02 kg/m2. 60.0% had hypertension, and 62.42% had diabetes. In this study 64 patients with acute ischemic stroke (38.79%) were found to have hypoalbuminemia. Conclusion: In light of these results, serum albumin may be a useful biomarker for acute ischemic stroke patient’s risk classification.